A preparation method of wear-resistant modified EVA foam sole material

By blending POE grafted microcrystalline cellulose with EVA and reducing the hydrophilicity of the material with fluoroacyl chloride crosslinking agent, the problem of insufficient strength and wear resistance of traditional EVA foaming materials is solved, and the mechanical properties and water resistance of the material are significantly improved.

CN119039651BActive Publication Date: 2025-03-07赛纳(苏州)安防用品有限公司

Patent Information

Application Number
CN202411548216.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-01
Publication Date
2025-03-07
Estimated Expiration
2044-11-01

AI Technical Summary

Technical Problem

Traditional EVA foaming materials have problems of low strength and poor wear resistance, which affects their practical application in foamed shoe materials and other fields.

Method used

By blending and foaming POE grafted microcrystalline cellulose with ethylene-vinyl acetate copolymer EVA, and using fluoroacyl chloride crosslinking agent to reduce the hydrophilicity of microcrystalline cellulose, forming a hydrophobic network, and improving the water resistance and waterproofing performance of the material.

Benefits of technology

The tensile strength, elongation of break and tear strength of foamed materials are significantly improved, the relative volume wear is reduced, the wear resistance is improved, and the water resistance and water resistance of the material is enhanced.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure QLYQS_1
    Figure QLYQS_1
Patent Text Reader

Abstract

The present invention relates to the technical field of EVA, and discloses a preparation method of a wear-resistant modified EVA foamed sole material, ethylene-vinyl acetate copolymer, POE grafted microcrystalline cellulose, ethylene propylene diene monomer rubber, auxiliary agent, filler, cross-linking agent, foaming agent are placed in an open mill, and molded foaming is carried out in a flat vulcanizer after mixing to obtain a wear-resistant modified EVA foamed sole material. POE can play the role of a compatibilizer, improve the interface compatibility between microcrystalline cellulose and EVA, improve the tensile strength, elongation at break and tear strength of the foamed material, and reduce the relative volume wear amount, improve wear resistance. And reduce water absorption, improve the water resistance and waterproof performance of the foamed sole material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of EVA, in particular to a method for preparing a wear-resistant modified EVA foamed sole material. Background Art

[0002] EVA is an ethylene-vinyl acetate copolymer with good foaming properties, high elasticity, high toughness, and good impact resistance. It is widely used in the fields of foamed shoe materials, packaging molds, hot melt adhesives, wires and cables, etc. Traditional EVA foam materials have problems such as low strength and poor wear resistance, which are not conducive to the practical application of EVA in foamed shoe materials, etc. Usually, inorganic fillers or high-performance polymers need to be added to improve the mechanical properties of EVA foam materials.

[0003] Cellulose is a cheap, easily available, green and environmentally friendly macromolecular polymer material, which is widely used in plastics, rubber and other polymer materials to improve the mechanical strength, wear resistance and other properties of the materials. Patent CN106117766B discloses the use of silane coupling agent to modify wood cellulose powder, and then mix it with hydrogenated styrene butadiene polymer, ethylene-vinyl acetate copolymer, foaming agent, bridging agent, activator, etc., to obtain EVA foam material with light weight, durability, shock absorption, high elasticity, tear resistance and other properties. However, ordinary cellulose has a high hydrophilicity, and adding it to EVA will affect the water resistance and waterproof properties of the foam material. Summary of the invention

[0004] (I) Technical Problems Solved: The present invention provides a method for preparing a wear-resistant modified EVA foam sole material, which solves the problem of poor wear resistance of the EVA foam material and improves the water resistance and waterproof performance of the EVA foam material.

[0005] (II) Technical solution: A method for preparing a wear-resistant modified EVA foam sole material, comprising the following steps:

[0006] S1. Add N,N-dimethylacetamide, pyridine, microcrystalline cellulose, and hydroxyethyl methacrylate grafted POE into a flask, introduce nitrogen after stirring, add a fluorinated acyl chloride crosslinking agent, stir to react, pour the solution into ethanol, filter after stirring, wash with ethanol and water in turn, and dry to obtain POE grafted microcrystalline cellulose.

[0007] S2. Add 100 parts by weight of ethylene-vinyl acetate copolymer into an open mill, and knead at 80-90°C, then add 15-30 parts by weight of POE grafted microcrystalline cellulose and 8-25 parts by weight of ethylene propylene diene rubber, and mix, then add 1-1.3 parts by weight of an auxiliary agent, 3-6 parts by weight of a filler, and 2-2.6 parts by weight of a cross-linking agent, and after mixing, add 2.3-2.8 parts by weight of a foaming agent, and after mixing, produce a sheet, and place it in a flat vulcanizer for compression foaming to obtain a wear-resistant modified EVA foamed sole material.

[0008] Preferably, the volume amount of pyridine is 25-40% of the volume of N,N-dimethylacetamide.

[0009] Preferably, the mass of hydroxyethyl methacrylate grafted POE and the fluorine-containing acyl chloride crosslinking agent in S1 is 6-20% and 10-30% of the mass of microcrystalline cellulose, respectively.

[0010] Preferably, the reaction in S1 is carried out at 50-80° C. for 18-36 h.

[0011] Preferably, the filler in S2 is calcium carbonate or talc; the auxiliary agent is stearic acid, the cross-linking agent is diisopropylbenzene peroxide, and the foaming agent is azodicarbonamide.

[0012] Preferably, the pressure during the compression foaming in S2 is 10-20 MPa, the temperature is 165-175° C., and the time is 6-10 min.

[0013] Preferably, the preparation method of the fluorine-containing acyl chloride cross-linking agent is:

[0014] (1) Add dichloromethane, chloroform or tetrahydrofuran solvent in a molar ratio of 1:(2-2.6):(0.07-0.1) to a flask equipped with a condenser reflux tube, phthalic anhydride, 4-dimethylaminopyridine, stir and react at 40-65°C for 5-8h, distill under reduced pressure, and recrystallize the product from ethyl acetate to obtain an intermediate.

[0015] (2) Add thionyl chloride and the intermediate in a molar ratio of (18-24):1 to a flask equipped with a condenser reflux tube, stir and react at 65-75°C for 3-5 hours, distill under reduced pressure, and dry to obtain a fluorinated acyl chloride crosslinking agent. The reaction formula is as follows:

[0016]

[0017] Preferably, the preparation method of hydroxyethyl methacrylate grafted POE is: add ethylene-α-olefin copolymer POE, 3-8% hydroxyethyl methacrylate and 0.2-0.6% diisopropylbenzene peroxide of the mass of ethylene-α-olefin copolymer POE into an internal mixer, carry out melt grafting at 140-150°C for 5-10 minutes, discharge the material, then dissolve it in xylene, add methanol to precipitate, filter and dry it to obtain hydroxyethyl methacrylate grafted POE.

[0018] (III) Technical effect: The present invention uses 4-dimethylaminopyridine as a catalyst to react hexafluorobisphenol A and phthalic anhydride, and then chlorinates with thionyl chloride to obtain a fluorine-containing acyl chloride crosslinking agent. The acyl chloride group reacts with the hydroxyl group of microcrystalline cellulose and the hydroxyl group of hydroxyethyl methacrylate grafted POE, thereby grafting POE onto the surface of microcrystalline cellulose to obtain POE grafted microcrystalline cellulose.

[0019] The present invention uses ethylene-vinyl acetate copolymer as the base material of the foamed sole material, and blends and foams it with POE-grafted microcrystalline cellulose, EPDM rubber, fillers, foaming agents, crosslinking agents, etc. Since POE and EVA have good compatibility, POE can play the role of a compatibilizer, improve the interface compatibility between microcrystalline cellulose and EVA, make the microcrystalline cellulose have a better reinforcement effect, significantly improve the tensile strength, elongation at break and tear strength of the foamed material, reduce the relative volume abrasion, and improve the wear resistance.

[0020] The fluorine-containing acyl chloride crosslinking agent of the present invention contains multiple hydrophobic fluorine-containing groups and benzene rings, which is beneficial to reducing the hydrophilicity of microcrystalline cellulose. When added to EVA, it forms a hydrophobic network in the foaming material, reduces the water absorption rate, and improves the water resistance and waterproof performance of the foaming sole material. DETAILED DESCRIPTION

[0021] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by ordinary technicians in the technical field to which the present invention belongs.

[0022] The ethylene-vinyl acetate copolymer of the present invention is from Suzhou Yitianli Plastic Co., Ltd. Ethylene-α-olefin copolymer POE is from Suzhou Yitianli Plastic Co., Ltd. Microcrystalline cellulose is from Jiangsu Maige Biotechnology Co., Ltd. EPDM is from Dongguan Chengjin Plastics Co., Ltd.

[0023] Example 1

[0024] (1) Add 50 mL of tetrahydrofuran solvent, 8 mmol of hexafluorobisphenol A, 17.6 mmol of phthalic anhydride, and 0.8 mmol of 4-dimethylaminopyridine to a flask equipped with a condenser reflux tube, stir and react at 65°C for 5 h, distill under reduced pressure, and recrystallize the product from ethyl acetate to obtain an intermediate.

[0025] (2) Add 120 mmol of thionyl chloride and 5 mmol of the intermediate into a flask equipped with a condenser reflux tube, stir and react at 75°C for 4 hours, distill under reduced pressure, and dry to obtain a fluorinated acyl chloride cross-linking agent.

[0026] (3) Add 50g of ethylene-α-olefin copolymer POE, 2.5g of hydroxyethyl methacrylate and 0.14g of diisopropylbenzene peroxide into an internal mixer, carry out melt grafting at 150°C for 8min, discharge the material, dissolve it in xylene, add methanol to precipitate, filter and dry it to obtain hydroxyethyl methacrylate grafted POE.

[0027] (4) Add 800 mL of N,N-dimethylacetamide, 250 mL of pyridine, 50 g of microcrystalline cellulose, and 3 g of hydroxyethyl methacrylate grafted POE into a flask, introduce nitrogen after stirring, add 5 g of fluorinated acyl chloride crosslinking agent, stir and react at 80°C for 18 h, pour the solution into ethanol, stir and filter, wash with ethanol and water in turn, and dry to obtain POE grafted microcrystalline cellulose.

[0028] (5) Add 1000g of ethylene-vinyl acetate copolymer into an open mill and knead at 80°C. Then add 150g of POE grafted microcrystalline cellulose and 80g of EPDM rubber and mix them. Then add 12g of stearic acid as an auxiliary agent, 60g of calcium carbonate as a filler, and 20g of diisopropylbenzene peroxide as a cross-linking agent. After mixing, add 25g of azodicarbonamide as a foaming agent. After mixing, produce a sheet, place it in a flat vulcanizer, and mold it for foaming at 175°C for 6min under a pressure of 15MPa to obtain a wear-resistant modified EVA foam sole material.

[0029] Example 2

[0030] (1) Add 40 mL of dichloromethane solvent, 8 mmol of hexafluorobisphenol A, 20.8 mmol of phthalic anhydride, and 0.56 mmol of 4-dimethylaminopyridine to a flask equipped with a condenser reflux tube, stir and react at 40°C for 8 h, distill under reduced pressure, and recrystallize the product from ethyl acetate to obtain an intermediate.

[0031] (2) Add 90 mmol of thionyl chloride and 5 mmol of the intermediate into a flask equipped with a condenser reflux tube, stir and react at 65°C for 5 hours, distill under reduced pressure, and dry to obtain a fluorinated acyl chloride cross-linking agent.

[0032] (3) Add 50g of ethylene-α-olefin copolymer POE, 1.5g of hydroxyethyl methacrylate and 0.1g of diisopropylbenzene peroxide into an internal mixer, carry out melt grafting at 150°C for 5min, discharge the material, dissolve it in xylene, add methanol to precipitate, filter and dry it to obtain hydroxyethyl methacrylate grafted POE.

[0033] (4) Add 800 mL of N,N-dimethylacetamide, 200 mL of pyridine, 50 g of microcrystalline cellulose, and 7 g of hydroxyethyl methacrylate grafted POE into a flask, introduce nitrogen after stirring, add 10 g of fluorinated acyl chloride crosslinking agent, stir and react at 50°C for 36 hours, pour the solution into ethanol, stir and filter, wash with ethanol and water in turn, and dry to obtain POE grafted microcrystalline cellulose.

[0034] (5) Add 1000g of ethylene-vinyl acetate copolymer into an open mill and mix at 80°C. Then add 300g of POE grafted microcrystalline cellulose and 80g of EPDM rubber and mix them. Then add 10g of stearic acid as an auxiliary agent, 30g of talc as a filler, and 26g of diisopropylbenzene peroxide as a cross-linking agent. After mixing, add 23g of azodicarbonamide as a foaming agent. After mixing, the sheet is formed and placed in a flat vulcanizer. Under a pressure of 10MPa, the sheet is molded and foamed at 175°C for 6min to obtain a wear-resistant modified EVA foam sole material.

[0035] Example 3

[0036] (1) Add 50 mL of chloroform solvent, 8 mmol of hexafluorobisphenol A, 16 mmol of phthalic anhydride, and 0.8 mmol of 4-dimethylaminopyridine to a flask equipped with a condenser reflux tube, stir and react at 50°C for 7 h, distill under reduced pressure, and recrystallize the product from ethyl acetate to obtain an intermediate.

[0037] (2) Add 100 mmol of thionyl chloride and 5 mmol of the intermediate into a flask equipped with a condenser reflux tube, stir and react at 75°C for 3 hours, distill under reduced pressure, and dry to obtain a fluorinated acyl chloride cross-linking agent.

[0038] (3) Add 50g of ethylene-α-olefin copolymer POE, 4g of hydroxyethyl methacrylate and 0.3g of diisopropylbenzene peroxide into an internal mixer, carry out melt grafting at 140°C for 10min, discharge the material, dissolve it in xylene, add methanol to precipitate, filter and dry it to obtain hydroxyethyl methacrylate grafted POE.

[0039] (4) Add 800 mL of N,N-dimethylacetamide, 320 mL of pyridine, 50 g of microcrystalline cellulose, and 10 g of hydroxyethyl methacrylate grafted POE into a flask, introduce nitrogen after stirring, add 15 g of fluorinated acyl chloride crosslinking agent, stir and react at 65 °C for 36 h, pour the solution into ethanol, stir and filter, wash with ethanol and water in turn, and dry to obtain POE grafted microcrystalline cellulose.

[0040] (5) Add 1000g of ethylene-vinyl acetate copolymer into an open mill and mix at 90°C. Then add 220g of POE grafted microcrystalline cellulose and 130g of EPDM rubber and mix. Then add 13g of stearic acid as an auxiliary agent, 50g of calcium carbonate as a filler, and 26g of diisopropylbenzene peroxide as a cross-linking agent. After mixing, add 28g of azodicarbonamide as a foaming agent. After mixing, produce a sheet, place it in a flat vulcanizer, and mold it at 165°C for 10 minutes under a pressure of 20MPa to obtain a wear-resistant modified EVA foam sole material.

[0041] Comparative Example 1

[0042] (1) Add 1000g of ethylene-vinyl acetate copolymer into an open mill and mix at 80°C, then add 80g of ethylene propylene diene monomer rubber and mix, then add 12g of stearic acid as an auxiliary agent, 60g of calcium carbonate as a filler, and 20g of diisopropylbenzene peroxide as a cross-linking agent, and add 25g of azodicarbonamide as a foaming agent after mixing. After mixing, the sheet is produced and placed in a flat vulcanizer for compression molding and foaming at 175°C for 6min under a pressure of 15MPa to obtain a wear-resistant modified EVA foam sole material.

[0043] Comparative Example 2

[0044] (1) Add 1000g of ethylene-vinyl acetate copolymer into an open mill and knead at 80°C, then add 150g of microcrystalline cellulose and 80g of EPDM rubber and mix them, then add 12g of stearic acid as an auxiliary agent, 60g of calcium carbonate as a filler, and 20g of diisopropylbenzene peroxide as a cross-linking agent, and add 25g of azodicarbonamide as a foaming agent after mixing. After mixing, the sheet is produced and placed in a flat vulcanizer for mold foaming at 175°C for 6min under a pressure of 15MPa to obtain a wear-resistant modified EVA foamed sole material.

[0045] Comparative Example 3

[0046] (1) Add 800 mL of N,N-dimethylacetamide, 250 mL of pyridine, 50 g of microcrystalline cellulose, and 3 g of ethylene-α-olefin copolymer POE into a flask, introduce nitrogen after stirring, add 5 g of fluorinated acyl chloride crosslinking agent, stir and react at 80°C for 18 h, pour the solution into ethanol, stir and filter, wash with ethanol and water in turn, and dry to obtain POE-microcrystalline cellulose.

[0047] (2) Add 1000g of ethylene-vinyl acetate copolymer into an open mill and mix at 80°C. Then add 150g of POE-microcrystalline cellulose and 80g of EPDM rubber and mix. Then add 12g of stearic acid as an auxiliary agent, 60g of calcium carbonate as a filler, and 20g of diisopropylbenzene peroxide as a cross-linking agent. After mixing, add 25g of azodicarbonamide as a foaming agent. After mixing, produce a sheet, place it in a flat vulcanizer, and mold it for foaming at 175°C for 6min under a pressure of 15MPa to obtain a wear-resistant modified EVA foam sole material.

[0048] Comparative Example 4

[0049] (1) Add 50g of ethylene-α-olefin copolymer POE, 2.5g of hydroxyethyl methacrylate and 0.14g of diisopropylbenzene peroxide into an internal mixer, carry out melt grafting at 150°C for 8min, discharge the material, dissolve it in xylene, add methanol to precipitate, filter and dry it to obtain hydroxyethyl methacrylate grafted POE.

[0050] (2) Add 800 mL of N,N-dimethylacetamide, 250 mL of pyridine, 50 g of microcrystalline cellulose, and 3 g of hydroxyethyl methacrylate grafted POE into a flask, introduce nitrogen after stirring, add 5 g of terephthaloyl chloride, stir and react at 80°C for 18 h, pour the solution into ethanol, stir and filter, wash with ethanol and water in turn, and dry to obtain POE grafted microcrystalline cellulose.

[0051] (3) Add 1000g of ethylene-vinyl acetate copolymer into an open mill and mix at 80°C. Then add 150g of POE grafted microcrystalline cellulose and 80g of EPDM rubber and mix them. Then add 12g of auxiliary agent stearic acid, 60g of filler calcium carbonate, and 20g of cross-linking agent diisopropylbenzene peroxide. After mixing, add 25g of foaming agent azodicarbonamide. After mixing, the sheet is produced and placed in a flat vulcanizer. Under a pressure of 15MPa, the sheet is molded and foamed at 175°C for 6min to obtain a wear-resistant modified EVA foam sole material.

[0052] The relative volume wear and wear resistance of the wear-resistant modified EVA foam sole material were tested according to GB / T 9867-2008 standard.

[0053] The tensile properties are tested according to GB / T 6344-2008 standard.

[0054] The tear strength was tested according to GB / T 10808-2006.

[0055] The wear-resistant modified EVA foam sole material is made into a 20cm×8cm×2cm sample, dried, and weighed; completely immersed in water for 48 hours at a water temperature of 25°C. After immersion, the sample is taken out, the surface moisture is wiped off, and dried, and the water absorption rate W is calculated. W=(m-m0) / m0×100%. m0 is the mass of the sample before immersion. m is the mass after immersion.

[0056] Table 1

[0057]

[0058] As can be seen from the table above, compared with Comparative Example 1, Comparative Example 2 adds microcrystalline cellulose. Due to the poor compatibility between microcrystalline cellulose and ethylene-vinyl acetate copolymer EVA, after blending and foaming, the dispersion in the EVA foam material is not good, the reinforcement effect on the foam material is not good, the increase in tensile strength, elongation at break and tear strength is low, the relative volume abrasion is large, and the wear resistance is poor. In addition, microcrystalline cellulose is a hydrophilic substance. When added to EVA, it will increase the water absorption rate of the foam material and reduce the water resistance and waterproof performance.

[0059] In Examples 1-3, the acyl chloride group of the fluorinated acyl chloride crosslinking agent is reacted with the hydroxyl group of microcrystalline cellulose and the hydroxyl group of POE grafted with hydroxyethyl methacrylate, so that POE is grafted to the surface of the microcrystalline cellulose. Since POE and EVA have good compatibility, POE can play the role of a compatibilizer, thereby improving the interfacial compatibility between microcrystalline cellulose and EVA, making the microcrystalline cellulose have a better reinforcement effect, significantly improving the tensile strength, elongation at break and tear strength of the foamed material, reducing the relative volume abrasion, and improving the wear resistance. At the same time, the fluorinated acyl chloride crosslinking agent contains multiple hydrophobic fluorinated groups and benzene rings, which is beneficial to reducing the hydrophilicity of microcrystalline cellulose. When added to EVA, a hydrophobic network is formed in the foamed material, which reduces the water absorption rate and improves the water resistance and waterproofing performance.

[0060] The ethylene-α-olefin copolymer POE of Comparative Example 3 does not contain hydroxyl groups and cannot undergo cross-linking reaction with microcrystalline cellulose and fluorine-containing acyl chloride cross-linking agent, resulting in the inability to graft POE molecular chains onto microcrystalline cellulose. The obtained POE-microcrystalline cellulose is in a physical blend state of the two. POE cannot play the role of a compatibilizer, and it is difficult to effectively improve the interfacial compatibility between microcrystalline cellulose and EVA. The reinforcing effect of microcrystalline cellulose is not good, the tensile strength, elongation at break and tear strength of the foamed material are low, the relative volume abrasion is large, and the wear resistance is poor.

[0061] In Comparative Example 4, terephthaloyl chloride is used to cross-link POE with microcrystalline cellulose and hydroxyethyl methacrylate to graft POE, thereby grafting POE onto the surface of microcrystalline cellulose, improving the interfacial compatibility between microcrystalline cellulose and EVA, and making the microcrystalline cellulose have a good reinforcement effect, thereby improving the tensile strength, elongation at break and tear strength of the foamed material, reducing the relative volume abrasion, and improving the wear resistance. However, terephthaloyl chloride does not contain hydrophobic fluorine-containing groups, resulting in a large water absorption rate of the foamed material and poor water resistance and waterproofing properties.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A method for preparing a wear-resistant modified EVA foam sole material, characterized in that: The preparation method comprises the following steps: S1. Add N,N-dimethylacetamide, pyridine, microcrystalline cellulose, and hydroxyethyl methacrylate grafted POE into a flask, introduce nitrogen after stirring, add a fluorine-containing acyl chloride crosslinking agent, stir to react, pour the solution into ethanol, stir, filter, wash, and dry to obtain POE grafted microcrystalline cellulose; The structural formula of the fluorine-containing acyl chloride cross-linking agent is: ; S2, adding 100 parts by weight of ethylene-vinyl acetate copolymer to an open mill, mixing at 80-90° C., then adding 15-30 parts by weight of POE grafted microcrystalline cellulose and 8-25 parts by weight of ethylene propylene diene monomer rubber, mixing, then adding 1-1.3 parts by weight of an auxiliary agent, 3-6 parts by weight of a filler, and 2-2.6 parts by weight of a cross-linking agent, adding 2.3-2.8 parts by weight of a foaming agent after mixing, discharging a sheet after mixing, placing it in a flat vulcanizer for compression foaming, and obtaining a wear-resistant modified EVA foamed sole material; The masses of hydroxyethyl methacrylate grafted POE and fluorine-containing acyl chloride crosslinking agent in S1 are 6-20% and 10-30% of the mass of microcrystalline cellulose respectively.

2. The method for preparing the wear-resistant modified EVA foam sole material according to claim 1, characterized in that: The volume usage of the pyridine is 25-40% of the volume of N,N-dimethylacetamide.

3. The method for preparing the wear-resistant modified EVA foam sole material according to claim 1, characterized in that: The reaction in S1 is carried out at 50-80° C. for 18-36 h.

4. The method for preparing the wear-resistant modified EVA foam sole material according to claim 1, characterized in that: The filler in S2 is calcium carbonate or talcum powder; the auxiliary agent is stearic acid, the crosslinking agent is dicumyl peroxide, and the foaming agent is azodicarbonamide.

5. The method for preparing the wear-resistant modified EVA foam sole material according to claim 1, characterized in that: The pressure during the molding foaming in S2 is 10-20 MPa, the temperature is 165-175° C., and the time is 6-10 min.

6. The method for preparing the wear-resistant modified EVA foam sole material according to claim 1, characterized in that: The preparation method of the fluorine-containing acyl chloride cross-linking agent is: (1) Add solvent to a flask equipped with a condenser reflux tube, with a molar ratio of 1: (2-2.6): (0.07-0.1) hexafluorobisphenol A, phthalic anhydride, and 4-dimethylaminopyridine, stir and react at 40-65°C for 5-8 hours, distill under reduced pressure, and recrystallize to obtain an intermediate; (2) Add thionyl chloride and the intermediate in a molar ratio of (18-24):1 into a flask equipped with a condenser reflux tube, stir and react at 65-75°C for 3-5 hours, distill under reduced pressure, and dry to obtain a fluorine-containing acyl chloride cross-linking agent.

7. The method for preparing the wear-resistant modified EVA foam sole material according to claim 6, characterized in that: The solvent is dichloromethane, chloroform or tetrahydrofuran.

8. The method for preparing the wear-resistant modified EVA foam sole material according to claim 1, characterized in that: The preparation method of the hydroxyethyl methacrylate grafted POE is as follows: ethylene-α-olefin copolymer POE, hydroxyethyl methacrylate, and diisopropylbenzene peroxide are added into an internal mixer, melt grafting is performed at 140-150° C. for 5-10 minutes, the material is discharged, then dissolved in xylene, methanol is added to precipitate, filtered, and then dried to obtain the hydroxyethyl methacrylate grafted POE.

9. The method for preparing the wear-resistant modified EVA foam sole material according to claim 8, characterized in that: The masses of the hydroxyethyl methacrylate and dicumyl peroxide are 3-8% and 0.2-0.6% of the mass of the ethylene-α-olefin copolymer POE, respectively.

Citation Information

Patent Citations

  • A high-resilience, aging-resistant EVA foam material and its preparation method

    CN106117766B

  • EVA (ethylene vinyl acetate) shoe material foaming material and preparation method thereof

    CN108586904A

  • EVA (ethylene vinyl acetate) insole and preparation method thereof

    CN108586905A

Cited By

  • EVA / POE composite high-resilience foaming material and preparation method thereof

    CN120623628A

  • Eva / poe composite high resilience foam material and preparation method thereof

    CN120623628B